Effects of Several Synthesis Conditions on Bond Strength of Plywood Adhered with Natural Rubber Latex – Styrene Adhesive - Euis Hermiati; Widya Fatriasari; Faizatul Falah (Masyarakat Peneliti Kayu Indonesia, 2006)
This report discusses the effects of synthesis conditions on bond strength of plywood adhered with natural rubber latex - styrene adhesive. Synthesis variables observed were catalyst (with and without catalyst), pre-stirring (0 and 3 hours) and heating time (1 and 2 hours). Three-ply plywood samples were prepared from Albizia (Paraserianthes falcataria) and Red meranti (Shorea, sp.) veneers and their gluability were evaluated in accordance to Indonesian Standard (SNI 01-2704-1992). The results revealed that synthesis conditions (i.e. catalyst, pre-stirring and heating time) did not significantly influence the bond strength of plywood. Natural rubber latex – styrene adhesive is very appropriate as adhesive for Red meranti plywood. Nevertheless, it can be used as limited interior application for Albizia plywood. An addition of 10% phenol formaldehyde (PF) in natural rubber latex - styrene adhesive slightly improved the exterior type bond strength of Red meranti plywood